A glycoconjugate of Haemophilus influenzae Type b capsular polysaccharide with tetanus toxoid protein: hydrodynamic properties mainly influenced by the carbohydrate - Abdelhameed, Ali Saber; Adams, Gary G.; Morris, Gordon A.; Almutairi, Fahad M.; Duvivier, Pierre; Conrath, Karel; Harding, Stephen E. (Nature Publishing Group, 2016)
Three important physical properties which may affect the performance of glycoconjugate vaccines against serious disease are molar mass (molecular weight), heterogeneity (polydispersity), and conformational flexibility in solution. The dilute solution behaviour of native and activated capsular polyribosylribitol (PRP) polysaccharides extracted from Haemophilus influenzae type b (Hib), and the corresponding glycoconjugate made by conjugating this with the tetanus toxoid (TT) protein have been characterized and compared using a combination of sedimentation equilibrium and sedimentation velocity in the analytical ultracentrifuge with viscometry. The weight average molar mass of the activated material was considerably reduced (Mw ~ 0.24 × 106 g.mol−1) compared to the native (Mw ~ 1.2 × 106 g.mol−1). Conjugation with the TT protein yielded large polydisperse structures (of Mw ~ 7.4 × 106 g.mol−1), but which retained the high degree of flexibility of the native and activated polysaccharide, with frictional ratio, intrinsic viscosity, sedimentation conformation zoning behaviour and persistence length all commensurate with highly flexible coil behaviour and unlike the previously characterised tetanus toxoid protein (slightly extended and hydrodynamically compact structure with an aspect ratio of ~3). This non-protein like behaviour clearly indicates that it is the carbohydrate component which mainly influences the physical behaviour of the glycoconjugate in solution.